Aksi Separatisme Papua dan Cara Menanggulanginya - Miswah, Miswah Miswah (Maliki Interdisciplinary Journal, 2025)
Governance in countries is difficult to avoid, even Indonesia often experiences divisiveness from groups, national and region recorded in its history, but many governments have been able to overcome it. Although much has been overcome by the government, there is an ongoing movement of the free Papua movement known as opm (the Papua independent organization) and also known as KKB (an armed criminal group). The government has made extensive efforts to quell the anger of the papuan people to stop the sectarians from addressing the case, but it is unfortunate that the government’s attempts at handling the case were found to be incorrect because many of the human rights abuses that were not accurate in solving the problem of inequality. Some of the factors that have fueled the Papuan’s continued mobility to this day are economic, educational, health and social inequality factors, which Papua feels in children’s slight or differentiated from other regions in Indonesia. President Jokowi has been following up on cases of opportunism by providing a priority agenda on which the government plans to build infrastructure building projects on roads. So that it can help people with access to distribution of goods that move the akti wheel.